2022
DOI: 10.3389/fped.2022.989526
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of serum vitamin D and LL-37 levels in infants with bacterial pneumonia

Abstract: ObjectiveTo investigate the significance of vitamin D and human antimicrobial peptide LL-37 in the occurrence and development of bacterial pneumonia in infants.MethodsFrom January 2021 to January 2022, 80 infants with bacterial pneumonia were selected, including 33 cases of gram-positive bacterial infection (GP) and 47 cases of gram-negative bacterial infection (GN). During the same period, 40 infants who underwent health examination in The Affiliated Hospital of Hangzhou Normal University served as the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies reported that LL‐37 exhibits modulation of immune and inflammatory factor secretion in inflammatory diseases, such as chronic obstructive pulmonary disease and pneumonia, 21,22 and neutralizes LPS and thus inhibits TLR4 signaling pathway 23 . Moreover, LL‐37 can also induce septic shock by activating NLRP3 inflammatory vesicles prompting the production of a series of inflammatory factors such as IL‐1β 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that LL‐37 exhibits modulation of immune and inflammatory factor secretion in inflammatory diseases, such as chronic obstructive pulmonary disease and pneumonia, 21,22 and neutralizes LPS and thus inhibits TLR4 signaling pathway 23 . Moreover, LL‐37 can also induce septic shock by activating NLRP3 inflammatory vesicles prompting the production of a series of inflammatory factors such as IL‐1β 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that LL-37 exhibits modulation of immune and inflammatory factor secretion in inflammatory diseases, such as chronic obstructive pulmonary disease and pneumonia (20,21), and neutralizes LPS and thus inhibits TLR4 signaling pathway (22).…”
Section: Ll-37 Stimulates Immune Inflammatory Responses In Hcaecs Cel...mentioning
confidence: 99%